2007
DOI: 10.1158/0008-5472.can-06-3875
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: mda-9/Syntenin Regulates the Metastatic Phenotype in Human Melanoma Cells by Activating Nuclear Factor-κB

Abstract: mda-9/Syntenin is a scaffolding PDZ domain-containing protein overexpressed in multiple human cancers that functions as a positive regulator of melanoma metastasis. Using a normal immortal human melanocyte cell line and weakly and highly metastatic human melanoma cell lines, we presently show that mda-9/syntenin initiates a signaling cascade that activates nuclear factor-KB (NF-KB) in human melanoma cells. As a consequence of elevated mda-9/syntenin expression, tumor cell growth and motility, fundamental compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
89
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 46 publications
1
89
0
Order By: Relevance
“…We next manipulated the expression levels of mda-9/syntenin in FM516-SV and M4Beu., with low metastatic potential, and T1P26 and 7GP, which generate a high frequency of spontaneous metastasis in immunosuppressed neonatal rats (9,17,18). As evident in Fig.…”
Section: Forced Expression or Inhibition Of Expression Of Mda-9/syntementioning
confidence: 74%
See 2 more Smart Citations
“…We next manipulated the expression levels of mda-9/syntenin in FM516-SV and M4Beu., with low metastatic potential, and T1P26 and 7GP, which generate a high frequency of spontaneous metastasis in immunosuppressed neonatal rats (9,17,18). As evident in Fig.…”
Section: Forced Expression or Inhibition Of Expression Of Mda-9/syntementioning
confidence: 74%
“…Theoretically, binding of MDA-9/syntenin to c-Src through its PDZ domain-binding motifs may enable MDA-9/syntenin to assemble large c-Src-FAK complexes, which greatly enhance activation of the c-Src-FAK complex, leading to amplification of p38/NF-B signaling pathways (7)(8)(9). In this study, we observed that stimulation of integrin signaling with fibronectin, which recruits the SH3 domain of c-Src to the cytoplasmic domain of integrin and eventually leads to c-Src activation (28), promoted the formation of an active c-Src-FAK signaling complex in melanoma cells overexpressing mda-9/syntenin from the small pool of c-Src proteins with which FAK was associated (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the signaling pathways underlying MMP-2 expression and activation, as induced by d-GM3, have not been elucidated. Activation of p38 signaling mediates transcriptional activation of MMP-2 and MMP-9 (36,37), but the role of p38 in tumor metastasis is controversial (for reviews, refs. 19,21,38].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of GAPDH was used as an internal control; C, the effects of uPAR expression on the expression and phosphorylation of FAK, Src, and PI3K were examined by immunoblotting. uPAR was either knocked down with 3 independent siRNA sequences (Table 1) pathway is likely involved in tumor suppression by negatively regulating cell survival and proliferation (21,38), it has been suggested that p38 can positively regulate cell adhesion, invasion, and metastasis in tumors, including melanomas (32,36,37,(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%